AMIR ABDULLO'S MARCH OF KHORAZM (Scientific journal of the Fergana State University, 2023)
In this article, the campaign of Amir Abdullah, the eldest son and crown prince of the ruler of Movarounnahr, Amir Kazaghan, to Khorezm is researched on the basis of historical sources and scientific literature. Amir Abdullah's views on statehood, based on this, the measures taken to strengthen the central authority and increase its influence, and the fact that they corresponded to the policy of Amir Kazaghan, were highlighted as the results of the analysis.